Extraction and characterization of pectin from the fruit peel of Benincasa hispida (Thunb.) cogn - La Ode Akbar Rasydy; Nita Rusdiana; Mira Eria Anggraini (Pharmaciana, 2022)
Pectin is a polysaccharide and a major component of most plant cell walls and the functions as an adsorbent, emulsifying agent, gelling agent, stabilizer, and gelling agent. one of which is by utilizing the skin of Bligo fruit (Benincasa hispida (Thunb.) Cogn). This study aims to determine the presence of pectin contained in the skin of Bligo fruit using a completely randomized design (CRD) using 4 variations. concentration of citric acid solvent (5%,7%,9% and 11%) with extraction time consisting of 4 levels (30, 60, 90 and 120 minutes). The characteristics of the pectin produced were determined including water content, ash content, equivalent weight, methoxyl content, galacturonic acid content, and degree of esterification. This type of research is experimental research in the laboratory. The results showed that the highest yield was obtained from 7% citric acid concentration with an extraction time of 60 minutes, the yield value was 9.8%. The characteristics of the pectin obtained included water content of 11.6% and 9.2%; ash content of 8.8% and 8.7%; equivalent weight of 797,448 mg and 761,035 mg; methoxyl content 2.561% and 2.466%; galacturonic acid content 117.088% and 112.281%; esterification degree of 12,417 and 12,469%. FTIR spectroscopy which was used to compare the results of the spectra of extracted pectin and standard pectin showed the similarity of each absorption functional group.